Taut and Visionary: The Poetry of Geoff Page and Les Murray - Tulip, James (LiNQ (Literature in North Queensland), 2016)
James Tulip reviews: Geoff Page, Darker and Lighter, Five Islands Press, 2001. ISBN 0 86418 723 8 Laurie Hergenhan & Bruce Clunies Ross (eds), The Poetry of Les Murray: Critical Essays, UQP, 2001. ISBN 0 7022 32912 Les Murray, recorded on October 22nd 2001 at The Audio Workshop, London. The Poetry Archive Ltd, Ball’s Green House, Minchinhampton, Gloucestershire, GL6 9AR, England.